The Digital Wallet Transactions during the Covid-19 Pandemic Investigating User Continuance Intention Using Digital Wallet-Based Payment Systems - Diny Fariha Zakhir; Eko Ganis Sukoharsono; Endang Mardiaty (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
This study aims to test and analyze the factors in the ECM and UTAUT 2 theory in explaining the continuance intention using digital wallets after the covid-19 pandemic ends. This research was conducted on 120 digital wallet users who used their digital wallet as a transaction tool during the Covid-19 pandemic. This research uses an online survey with the help of GoogleForm. The analysis of this study uses SEM analysis with the help of SmartPLS. The study results explain that confirmation is proven to affect performance expectations and satisfaction. Performance expectations in this study also affected satisfaction and continuance intention significantly. Effort expectations also influenced performance expectations and continuance intention significantly. This research proves that satisfaction and habit significantly influence continuance intention. This study failed to prove that social influence, facilitating conditions, hedonic motivation, and price values significantly influence users' ongoing continuance intention using the digital wallet they used during the Covid-19 pandemic. The results of this study can provide an overview of digital wallet users so that they can provide input to digital wallet providers to update, upgrade, and improve the sustainability of digital wallets. Government can also use the results of this research as steps to encourage positive habits of using digital wallets, such as campaigns or educational programs to promote the use of digital wallets and increase digital literacy in the community by providing training or support to increase understanding and user skills regarding the use of digital wallets and digital payments.